Anaerobic H2 production at elevated temperature (60 °C) by enriched mixed consortia from mesophilic sources - Karadag, Dogan (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Two different enriched mixed consortia from mesophilic sources were used for H-2 production from glucose at 60 degrees C. The variables were initial pH, nitrogen source, iron and sulfate. pH had a crucial effect and iron was slightly positive for the biohydrogen production performance of the mixed culture. On the other hand, H-2 production decreased with the increasing of ammonia, peptone and sulfate concentrations. Metabolic pathways of mixed culture were affected in different ways depending on the differences in microbial community. The PCR-DGGE and sequencing based microbial community analysis revealed that two enriched mixed cultures had different microbial diversity and both culture were dominated mainly by Thermoanaerobacterium species. (C) 2010 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Enrichment; Mixed culture; Thermoanaerobacterium; BIOLOGICAL HYDROGEN-PRODUCTION; BIOHYDROGEN PRODUCTION; WASTE-WATER; CULTURE; IRON; FERMENTATION; ENHANCEMENT; GROWTH; PH; Chemistry; Electrochemistry; Energy & Fuels